India's development strategy accidents, design and replicability - Nirvikar Singh (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2009)
This paper examines India's development strategy, and to what extent it may be considered a success. It provides a brief history of why and how the strategy was adopted, as well as of its implementation, including the role of initial conditions, such as human capital, geographical location, and infrastructure. It analyses the extent and reasons for success of the strategy, including policy, political economy, timing, and linkage of the strategy to economy-wide development. Particular attention is given to the relative roles of domestic and international actors, including the part played by foreign investment, trade, and other dimensions of openness. The paper considers the extent to which the strategy remains viable for the future, the challenges still faced, and what other strategies might be required. It concludes with possible lessons for other countries and their future development strategies.
Keywords: O1; O2; O53; 330; development strategy; industrial policy; political economy; economic development; Entwicklungsstrategie; Indien